Biomass integration for energy recovery and efficient use of resources: Tomsk Region. (15th November 2021) - Fan, Yee Van; Romanenko, Sergey; Gai, Limei; Kupressova, Ekaterina; Varbanov, Petar Sabev; Klemeš, Jiří Jaromír
Abstract: Resource recovery has an essential role in achieving sustainable development. This study aims to minimise the environmental footprint of biomass integration for energy recovery, where a wide range of biomass, including manure, residual and forest wood, are considered. The assessed case study is the Tomsk region in the Russian Federation, focusing on GHG (Greenhouse Gas) footprints (CO2, CH4, N2 O). The adapted clustering-based method suggested that biomass integration, consisting of 16 districts, can be divided into three major clusters. The clusters could facilitate further resource planning, considering the land-use footprint of different energy generation. This study identified biomass integration design with minimum GHG footprint (origin of biomass and transportation) of - 217 kt CO2 eq/y mainly contributed by the avoided methane from manure. Scenario 1, where the energy demand (3, 723 TJ/y) is solely fulfilled by forest wood, contributes to 85.73 kt CO2 eq/y. By limiting waste biomass (manure and residual) for local utilisation only (without integration), 60% higher GHG emission (- 90.2 kt CO2 eq/y) is identified compared to the identified solution with a minimum GHG footprint. The environmental sustainability of bioenergy is highly dependent on the type of biomass, transporting activities, and heating value. It is crucial to evaluate case by case situation in substituting fossil-based energy or other renewable energy. Highlights: A model to minimise the environmental footprint of biomass integration is developed. The land availability per unit of energy could further facilitate energy source selection. 60% lower GHG footprint can be achieved via biomass integration in Tomsk Region. The proposed network has a GHG footprint of- 217 kt/y contributed by the avoided GHG. Consideration of local factors aid by the end-user interface could rally the practicability.